Trabajo minero y control social durante el porfiriato. Los operarios de dos poblaciones contrastantes - Mentz, Brígida von (El Colegio de México, A.C., 2001)
This article analyzes the life of workers in two contrasting mining towns during the Porfiriato: El Oro and Sultepec. The author seeks to show the consequences of quick modernization of mining companies on the lives of workers, the regional characteristics of town and the heterogeneity of the mining working class. Of special interest is the subordination of workers to the company and to the State. However, the State applied intimidating and repressing policies, but unevenly, for restless workers in isolated towns in implied less political danger than those in modern cities, where strikes, riots and uprisings of the working calss were supported by certain sectors of the middle class.